Multibacilar lepromatous leprosy multibacillary in a patient from a non-endemic area of the Peruvian Amazon - Castañeda Reyna, Marco A. (2025)
A 63-year-old male patient from Tocache, a hamlet in the Department of San Martín, Perú. He began his illness 5 years prior to presentation, with conjunctival erythema in both eyes. This was followed by nasal secretion, skin lesions producing nasal deformity, as well as skin exfoliation and anesthesia of the fingers and feet. On the neurological examination, there was anesthesia involving hands and feet. Laboratory work revealed normocytic anemia, leukopenia, eosinophilia, and lymphopenia. There was presence of fecal Strongyloides stercoralis and Ascaris lumbricoides. Sinus X-ray revealed sinusitis, polyps, and keratitis. The electromyography was compatible with a sensory axonal polyneuropathy without motor involvement. Biopsies of the sural nerve and the affected musculature were performed, and positive acid-fast bacilli were identified.